2008
DOI: 10.1073/pnas.0804745105
|View full text |Cite
|
Sign up to set email alerts
|

β-Blockers alprenolol and carvedilol stimulate β-arrestin-mediated EGFR transactivation

Abstract: Recent evidence suggests that binding of agonist to its cognate receptor initiates not only classical G protein-mediated signaling, but also ␤-arrestin-dependent signaling. One such ␤-arrestin-mediated pathway uses the ␤1-adrenergic receptor (␤1AR) to transactivate the EGFR. To determine whether ␤-adrenergic ligands that do not activate G protein signaling (i.e., ␤-blockers) can stabilize the ␤1AR in a signaling conformation, we screened 20 ␤-blockers for their ability to stimulate ␤-arrestin-mediated EGFR tra… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

17
262
2
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
5
2
1

Relationship

1
7

Authors

Journals

citations
Cited by 250 publications
(282 citation statements)
references
References 44 publications
17
262
2
1
Order By: Relevance
“…For example, carvedilol has been shown to promote βAR-mediated EGFR transactivation in a β-arrestin-dependent manner (20). In HEK293 cells stably overexpressing FLAG-β 2 AR, ICL1-9 promoted EGFR transactivation, as monitored by receptor phosphorylation at EGFR Tyr 845 , comparable to what is observed with carvedilol (Fig.…”
Section: Icl1-9supporting
confidence: 56%
“…For example, carvedilol has been shown to promote βAR-mediated EGFR transactivation in a β-arrestin-dependent manner (20). In HEK293 cells stably overexpressing FLAG-β 2 AR, ICL1-9 promoted EGFR transactivation, as monitored by receptor phosphorylation at EGFR Tyr 845 , comparable to what is observed with carvedilol (Fig.…”
Section: Icl1-9supporting
confidence: 56%
“…Our current results with the ␤ 2 -AR Ϫ/Ϫ mice rule out biased agonism as the explanation because these mice lack a functional ␤ 2 -AR gene and are incapable of producing any ␤ 2 -AR signaling through any pathway. Further support for this is that we have shown that the biased agonist carvedilol, a drug capable of activating the ERK1/2 pathway and EGFR transactivation, but an inverse agonist at the classical G s pathway, was not as effective at reducing AHR as nadolol, an inverse agonist that did not activate ERK1/2 or produce EGFR transactivation (15,17,18).…”
Section: Discussionmentioning
confidence: 84%
“…Thus, inverse agonists inhibit all signaling through the receptor's classical signaling pathway. However, it has recently been shown that many inverse agonists are also capable of activating receptor signaling through alternative pathways (17)(18)(19). For example, many ␤-AR inverse agonists are capable of stimulating a G protein-independent, ␤-arrestindependent activation of ERK1/2 (17).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Inhibition of this signalling path promoted myocyte apoptosis. A G protein-independent process of EGFR transactivation may also occur with some β-blockers (e.g., alprenolol, carvedilol) in non-cardiac models (Kim et al, 2008), with these agents also known to protect against acute or long-term effects of myocardial I-R. Grisanti et al (2014) more recently identified EGFR involvement in compartment-specific signalling responses to the -agonist isoproterenol.…”
Section: Role Of the Egfr In Gpcr-triggered Cardioprotectionmentioning
confidence: 99%